2013
DOI: 10.2337/dc13-0387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Renal Glucose Reabsorption in Response to Dapagliflozin in Healthy Subjects and Subjects With Type 2 Diabetes

Abstract: OBJECTIVETo examine the effect of dapagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, on the major components of renal glucose reabsorption (decreased maximum renal glucose reabsorptive capacity [TmG], increased splay, and reduced threshold), using the pancreatic/stepped hyperglycemic clamp (SHC) technique.RESEARCH DESIGN AND METHODSSubjects with type 2 diabetes (n = 12) and matched healthy subjects (n = 12) underwent pancreatic/SHC (plasma glucose range 5.5–30.5 mmol/L) at baseline and after 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
270
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(288 citation statements)
references
References 25 publications
13
270
1
4
Order By: Relevance
“…A study in rodents with sergliflozin demonstrated that SGLT2 inhibition markedly reduced the Tm without significant change in the glucose threshold or splay (43). In contrast, in humans dapagliflozin produced a decrease in the Tm as well as a marked reduction in both the threshold and splay in diabetic and nondiabetic individuals (20) (Fig. 4).…”
Section: Mechanism Of Glucosuriamentioning
confidence: 99%
“…A study in rodents with sergliflozin demonstrated that SGLT2 inhibition markedly reduced the Tm without significant change in the glucose threshold or splay (43). In contrast, in humans dapagliflozin produced a decrease in the Tm as well as a marked reduction in both the threshold and splay in diabetic and nondiabetic individuals (20) (Fig. 4).…”
Section: Mechanism Of Glucosuriamentioning
confidence: 99%
“…72 ,73 Dapagliflozin reduces the TmG in people with type 2 diabetes, but most importantly, it reduces the renal threshold at which glucose spills into the urine to ~ 40 mg/dl. 74 Like canagliflozin, dapagliflozin is effective in lowering both FPG and PPG concentrations, resulting in an A1C reduction of ~ 0.7-0.8% with a starting A1C of ~ 8.0-8.2%. 73,75 Reduction in the mean day-long plasma glucose concentration resulted in improved tissue sensitivity to insulin by 25-30% and enhanced β-cell function by 90-100%, 76 from correction of glucotoxicity.…”
Section: Sglt-2 and Sglt-1 Inhibitorsmentioning
confidence: 99%
“…Given their mode of action, which is heavily dependent on the glucose filtered load and therefore on glomerular filtration rate (GFR) (15,16), the efficacy of SGLT2 inhibitors in reducing plasma glucose is expected to be decreased with decreasing renal function. Since glucose-lowering agents for patients with CKD stages 3 and 4 are limited and frequently require dose adjustments, the identification of the cutoff of estimated GFR (eGFR) below which clinically significant reductions in plasma glucose cannot be achieved with SGLT2 inhibitors is crucial.…”
Section: Glucose-lowering Efficacy Of Sglt2 Inhibitors In Patients Wimentioning
confidence: 99%
“…The main nonglycemic effects include blood pressure reduction and weight loss. Given the mode of action, the glucose-lowering efficacy of SGLT2 inhibitors depends on renal function and on plasma glucose levels (15,16).…”
mentioning
confidence: 99%